State of the Art Blockchain Enabled Smart Contract Applications in the University - Rustiana, Deden; Ramadhan, Dennis; Wibowo, Lucky; Nugroho, Anang Wahyu; Mahardika, Gagas (Blockchain Frontier Technology, 2023)
A comprehensive analysis is necessary for the implementation and use of smart contracts in companies. This overview clarifies how this technology is now being used and identifies problems that are preventing its usage in contemporary organizations. This paper offers an organized assessment of prior research that includes frameworks, techniques, functional prototypes, and simulations that show how smart contracts are used in businesses. This paper's main goal is to better understand how smart-contract technology is used in organizations today. While there is limited knowledge about how smart contracts are used in companies, there is significant progress being made in the development of the technology that supports them. In this work, we describe the characteristics of smart-contract applications in many current organization fields. We further examine and group issues that hinder the adoption of smart-contract applications.